Reduced phagocytic activity of polymorphonuclear leukocytes in alpha(1,3) fucosyltransferase VII-deficient mice - Bartůņková, J; Malý, P; Smetana, K; Sedivá, A; Klubal, R; Mayerová, D; Sedláçek, A; Splíchalová, V (APMIS, 2000)
Deficiencies in adhesion molecules or their counter-receptors in humans may have severe consequences as exemplified by leukocyte adhesion deficiency (LAD) I or II syndromes. Because such diseases occur with great rarity, animal models are valuable for studying the role of particular adhesion molecules and their natural ligands in immunity. We studied selected immune parameters and general health in mice with a defect in the sialyl-Lewis X antigen (selectin ligand) caused by disruption of the gene encoding alpha(1,3)fucosyltransferase VII (Fuc-TVII). Leukocytes from Fuc-TVII -/- and control mice were tested for adherence to cellophane membranes or polymer particles in vivo and phagocytic activity in vitro. While no difference in adherence was found, the number of neutrophil granulocytes in exudate induced by intraperitoneal injection of polymer beads was reduced in knock-out mice. Moreover, the phagocytic activity in Fuc-TVII -/- mice was significantly reduced. These animals have splenomegaly due to increased hematopoiesis and reduced weight but do not exhibit clinical signs of immunodeficiency. In conclusion, the lack of Fuc-TVII activity leads to several morphological and functional abnormalities without an impact on survival rate.
Keywords: LAD syndrom; Phagocytosis; Cell Adhesion; Fucosyltransferases; Candida albicans; Disease Models, Animal; myši inbrední C57BL; Cellophane; Neutrophils; Mice; buňky kostní dřeně; myši knockoutované; slezina; fagocytóza; modely nemocí na zvířatech; zvířata; membrány umělé; Bone Marrow Cells; neutrofily; Mice, Inbred DBA; Leukocyte-Adhesion Deficiency Syndrome; Mice, Knockout; myši; fukosyltransferasy; Membranes, Artificial; buněčná adheze; myši inbrední DBA; celofán; Spleen; Mice, Inbred C57BL; Animals